2014
DOI: 10.1007/978-81-322-1774-9_7
|View full text |Cite
|
Sign up to set email alerts
|

Nanonization Increases the Antileishmanial Efficacy of Amphotericin B: An Ex Vivo Approach

Abstract: With widespread resistance to pentavalent antimonial in the endemic eastern terai belt of Nepal and Bihar, India, Amphotericin B deoxycholate is now the first-line antileishmanial drug for the treatment of visceral leishmaniasis (VL). However, universal occurrence of infusion-related fever and rigors with amphotericin B (AmB), occasional serious life-threatening toxicities like cardiotoxicity, anaphylaxis, hypokalemia, and nephrotoxicity are major barriers to its use in areas with limited medical facilities. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…NPs supply potentially efficient and safe selective drug delivery as well as specific biomarker and/or imaging probe binding [23]. Furthermore, NP drug delivery systems not only enhance targeting ability, but also control drug release [24, 25]. Thus, NPs can deliver drugs very effectively to a target site to enhance efficacy and reduce side effects [26].…”
Section: Introductionmentioning
confidence: 99%
“…NPs supply potentially efficient and safe selective drug delivery as well as specific biomarker and/or imaging probe binding [23]. Furthermore, NP drug delivery systems not only enhance targeting ability, but also control drug release [24, 25]. Thus, NPs can deliver drugs very effectively to a target site to enhance efficacy and reduce side effects [26].…”
Section: Introductionmentioning
confidence: 99%
“…NPs offer potentially safe and efficient selective drug delivery, as well as specific biomarker and/or imaging probe binding (Dellinger et al, 2013). Furthermore, novel NPs drug delivery systems not only enhance the targeting capability of transitional drugs (Bao et al, 2015;Broz et al, 2008), but also improve the drug efficacy through slow and sustained release (Botella et al, 2011;Das Manandhar et al, 2014).…”
mentioning
confidence: 99%
“…However, the major disadvantage associated with all these drugs are high resistance, dose dependent toxicity, high cost and their storage in cooling condition make them stumbling block. Nanonization of amphotericin-B has also shown increased efficacy [24,25] and its carbon nanotube attached form made it suitable for targeted killing of leishmania parasite in both in vitro and in vivo experiments [26,27]. Recently, Pandey RK et al have reported imidazole and febrifugine analogues as an antileishmanial drug candidate against TR of L. donovani against their native use to treat human african trypanosomiasis and malaria respectively [4,28].…”
Section: Discussionmentioning
confidence: 97%